Textured concave anti-reflecting coating and convex back reflector to enhance the absorbance of amorphous Si solar cells. (1st May 2022) - Taha, T A; Sayed, Hassan; Aly, Arafa H; Elsayed, Hussein A
Abstract: This work provides efficient designs in each the anti-reflective coating (ARC) and back reflector for enhancing the absorption of amorphous silicon solar cells. ARC structures are designed from planar, concave, and textured concave surfaces. For the back reflector structures, we use the concepts of the photonic bandgap (PBG) structure and convex surface. The mainstay in designing the ARC is specifically depending on the presence of a gradual increase in the refractive index as the incident radiation travels from air to the cell to decrease the solar cell reflectivity. Thus, the arrangement of (SiO2 /Si3 N4 /SiC) layers is considered in designing the proposed ARC. The theoretical formalism of this study is based on the finite element method and transfer matrix method as well. The numerical results demonstrate the cell absorption based on the different configurations of the ARC and the back reflecting mirror. The investigated results show that the solar cell absorption increases by 34.92% at 520 nm by including the planar ARC. However, significant decrements are obtained with the increase of the angle of incidence for the planar ARC. Meanwhile, the concave and textured geometries provide a perfect solution towards the increase of cell absorption with the angle of incidence, especially at wavelengths smaller than 550 nm. For wavelengths greater than 550 nm, 3-unit cells with the convex geometry represent the optimum design of the back mirror to increase the cell absorption at these wavelengths. Finally, the textured concave ARC and convex back reflector through the amorphous Si solar cell present a good candidate for significant enhancements of the cell absorption and optical generation as well.